Educação sexual nas escolas brasileiras: uma análise teórica e integral - Vilas Boas, Paola Moraes (Brasil, 2025)
This work aimed to analyze scientific productions related to sex education in Brazilian schools, seeking to highlight the importance of addressing this theme in the school environment. The research used a bibliographic and documentary methodology, with analysis of 19 academic productions selected in the CAPES Thesis Bank. The results indicate that, despite its recognized relevance, sex education faces cultural, political and institutional barriers, hindering its systematic implementation. Challenges such as prejudice, lack of teacher preparation and resistance from sectors of society were identified, as well as significant benefits for the emotional, social and cognitive development of children and adolescents. This study highlights the need for more robust public policies, initial and continuing teacher training, and an interdisciplinary approach to overcome obstacles and consolidate sex education as an integral part of the Brazilian school curriculum.